Cutaneous ureterostomies in pigs: technical feasibility assessment - Prado, T. D.; Ribeiro, R. G.; Treichel, T. L. E.; De Nardi, A. B. [UNESP] (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2019)
Increased life expectancy of pets favors the occurrence of cancer, such as the urinary bladder ones. The aim of this study was to evaluate the feasibility of cutaneous ureterostomy technique in pigs after the total cystectomy compared to the technique of colonic ureterostomy, as well as detect and characterize possible infraoperative complications. For that, 20 pigs were used, divided into two groups. All patients underwent radical cystectomy and then the cutaneous or colonic ureterostomies. The technical feasibility was assessed during the procedures. The procedures compared were: the incision size, dieresis time, realization of urinary diversion and the synthesis time. Also, the estimated blood loss and the degree of difficulty in performing the preparation procedures of the ureters, ureteroanastomose site preparation and ureteroanastomose itself were compared. The results indicate that performing cutaneous ureterostomy was better than the colonic ureterostomy in relation to blood loss, incision size, and anastomosis performance. In contrast, ureterocolonostomy showed better results on the implementation of ureteral preparation. Thus, it was concluded that both techniques can be indicated as viable urinary diversions and the choice will depend on factors intrinsic to the surgeon and the patient.
Keywords: pig; anastomosis; bladder; neoplasm; ureter